Revival of Public Service Advertising through Unconventional Mediums - Gaur, Sugandha (Indian Journal of Marketing, 2013)
It is time advertising saved the world with innovation and creativity. People around the globe are now alarmed and are aware about the constant degradation of the environment and increase in other social problems. People across the globe are willing to put in their efforts for social and environmental causes. This change of attitude in consumers' approach has prompted advertisers and agencies to take a leap forward by helping consumers to contribute to a good cause in the most appropriate and interesting ways. By doing this, brands/organizations can rebuild strong connections and trust with the audience. Advertisers and NGOs today are very much familiar with the fact that the warning messages in TV commercials, hard-hitting headlines of daily adverts, and brilliantly made radio spots for public service messages can no longer lift up the spirits of the people. They also believe that nowadays, warning messages about social issues given by the conventional media can hardly get the desired response due to many reasons; therefore, the results are not pleasing. After observing the growing levels of social awareness and behavioral change in the present day consumers, advertisers have now decided to do something different on a social side to catch the attention of their consumers, and at the same time, do their bit for a good cause. Advertisers are now coming up with unconventional ways to make a difference and are also hiring renowned creative firms for their brands to do something innovative and productive for the present world. Hence, it is now up to brands and organizations to prove that they deserve to be trusted by the consumers, as it is high time for them to think about how they can add value to people's lives.